2014
DOI: 10.4172/2155-9562.1000236
|View full text |Cite
|
Sign up to set email alerts
|

Role of LDL Cholesterol and Endolysosomes in Amyloidogenesis and Alzheimer’s Disease

Abstract: The pathogenesis of late-onset sporadic Alzheimer's disease (AD) is believed to result from complex interactions between nutritional, environmental, epigenetic and genetic factors. Among those factors, altered circulating cholesterol homeostasis, independent of the APOE genotype, continues to be implicated in brain deposition of amyloid beta protein (Aβ) and the pathogenesis of AD. It is believed that trafficking of amyloid beta precursor protein (AβPP) into endolysosomes appears to play a critical role in det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 131 publications
(131 reference statements)
0
9
0
Order By: Relevance
“…However, we found that EPA or DHA at the same dose as ALA markedly decreased brain content of LDL, SFAs and AA. The accumulation of LDL and SFAs are highly related to the development of stroke, atherosclerosis, thrombosis or even neurodegenerative diseases [ 25 , 26 ]. Since EPA or DHA substantially lowered brain LDL and SFAs levels under aging condition, the intake of these two PUFAs may reduce the occurrence of the above disorders.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that EPA or DHA at the same dose as ALA markedly decreased brain content of LDL, SFAs and AA. The accumulation of LDL and SFAs are highly related to the development of stroke, atherosclerosis, thrombosis or even neurodegenerative diseases [ 25 , 26 ]. Since EPA or DHA substantially lowered brain LDL and SFAs levels under aging condition, the intake of these two PUFAs may reduce the occurrence of the above disorders.…”
Section: Discussionmentioning
confidence: 99%
“…This is to say, the increased prevalence and risk for AD among women can be explained in part by the abrupt decrease in estrogen production that accompanies the post-menopausal state. Not only does the lack of estrogen decrease concentrations of anti-inflammatory LC-PUFAs and HDL-C in the body, but it also increases TG levels, augmenting secretion of VLDL (very-low density lipoprotein), a lipid carrier known to induce neuroinflammation (Burgess et al, 2006;Chen et al, 2014;Nägga et al, 2018). Additionally, genetic factors, such as ApoE status, and social determinants, such as education, mental illness, and diet, interact with the post-menopausal state to amplify these detrimental effects, increasing risk of AD.…”
Section: Lipids and Sexmentioning
confidence: 99%
“…Consistent with this idea, APOE ε4, but not APOE ε3, in a thiorphan-treated APP mouse model of AD, expands lysosomal compartments, increases Aβ co-localization with lysosomes, and causes learning and memory impairment (Belinson et al, 2008). Cholesterol, the principal lipid carried into neurons by ApoE, and a suspected AD risk factor (Chen et al, 2014a; Chen et al, 2014b), also induces neuronal rab5 activation and endocytic upregulation when administered to animals through a high-fat diet (Braccini et al, 2015). Evidence suggests that membrane cholesterol may also influence v-ATPase function more directly.…”
Section: V-atpase –Related Lysosomal Acidification Failure In Diseasementioning
confidence: 99%